Three-Dimensional Nonlinear Seismic Response of Shield Tunnel Spatial End Structure - Yijing Lu; Yongsheng Song; Yanzhen Wang; Jiale Yuan (Advances in Civil Engineering)
The stiffness mutation of shield tunnel-shaft junction makes the tunnel structure affected by the differential displacement and forms a complex spatial effect. Taking the subsea shield tunnel crossing under the Shantou Gulf, China, as a case study, a three-dimensional finite element global model and a refined local spatial end submodel are established. The nonlinear dynamic behaviors of the seabed soil and concrete, the simulation of the bolt joints between ring segments by using cohesive models and the SMA shape memory alloy flexible joints, and the input ground motions produced by scaling from the high-level earthquake records are considered in detail. The results show that the shield tunnel spatial end structure increases nonlinearly in response to the increase of seismic motion intensity. The opening width and the deformation between ring segments at the vault and the outside spandrel are larger, and serious seismic damage and stress concentration exist at the conjugate 45° directions of shaft. The seismic responses of the tunnel-shaft junction subjected to the seismic motions with rich low-frequency components are much stronger than those of seismic motions with rich high-frequency components. Adding SMA flexible joints, the structural deformation caused by seismic motion propagation can be induced to the preset flexible joint, and the structural damage and stress concentration can be effectively reduced. The seismic response characteristics of shield tunnel spatial end structure calculated by the global model are consistent with those calculated by the submodel, while the seismic response of the submodel is greater than that of the global model.